The Role of Mediating Innovation and Social Media : Market Orientation and Entrepreneurial Orientation on the Performance of MSME’s Processed by Sea Products in Labuan Village, Banten - Muhammad Richo Rianto; Choiroel Woestho; Adi Wibowo Noor Fikri (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to see the effect of mediating innovation and Social Media that connects Market Orientation and Entrepreneurial Orientation to the Performance of MSMEs Processed by Sea Products in Labuan Banten Village. This study uses quantitative. The unit of analysis in this study is the perpetrators of MSMEs Processed Sea Products in Labuan Banten Village. This research was conducted on 135 and using the statistical tool SmartPLS 3.0 The results of this study emphasize that innovation can mediate the relationship between Market Orientation and Entrepreneurial Orientation and Social Media can mediate the relationship between Market Orientation but cannot mediate Entrepreneurial Orientation. In addition, market orientation affects the performance of marine processed SMEs in Labuan - Banten, entrepreneurial orientation affects the performance of marine processed SMEs in Labuan - Banten, innovation affects the performance of SMEs, social media orientation affects the performance of SMEs, market orientation affects the performance through innovation, entrepreneurial orientation affects the performance of SMEs mediated by innovation.